2005
DOI: 10.1016/j.bbrc.2005.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Th1 type response by DNA vaccinations with N, M, and E genes against SARS-CoV in mice

Abstract: Vaccination against the SARS-CoV infection is an attractive means to control the spread of viruses in public. In this study, we employed a DNA vaccine technology with the levamisole, our newly discovered chemical adjuvant, to generate Th1 type of response. To avoid the enhancement antibody issue, genes encoding the nucleocapsid, membrane, and envelope protein of SARS-CoV were cloned and their expressions in mammalian cells were determined. After the intramuscular introduction into animals, we observed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 31 publications
8
56
0
Order By: Relevance
“…In contrast, our current data suggest that N protein-immunized mice exhibit activation of both Th1 and Th2 responses after SARS-CoV infection. In agreement with our data, Jin et al (54) have demonstrated that prior immunization with N protein generates stronger Ag-specific Th1 and Th2 responses than immunization with M or E protein.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, our current data suggest that N protein-immunized mice exhibit activation of both Th1 and Th2 responses after SARS-CoV infection. In agreement with our data, Jin et al (54) have demonstrated that prior immunization with N protein generates stronger Ag-specific Th1 and Th2 responses than immunization with M or E protein.…”
Section: Discussionsupporting
confidence: 94%
“…We assume that antigen-specific CD8 + T cells reveal a direct killing of virus-infected cells and CD4 + T cells may provide help for antibody isotype switching and generation of memory B cells and memory CD8 + T cells [23,26]. In support of our expectation, other studies of animal coronavirus have suggested that both cellular and humoral immunity contribute to protection during persistent infection [27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 73%
“…In previous study, N protein is a representative antigen for the T-cell response in vaccine setting (Gao et al, 2003), and the mice vaccinated with calreticulin (CRT)/N DNA were capable of significantly reducing the titer of challenging vaccinia virus expressing the N protein of SARS virus (Kim et al, 2004). It has been reported that N DNA vaccine could induce SARS-specific T-cell proliferation and cytotoxic T cells activity, further experiments demonstrate that SARS-N administration could induce virus-specific cellular responses in human cells using SCID-PBL/hu mouse model (Jin et al, 2005;Okada et al, 2005). Although more than 90% of sera obtained from convalescent SARS patients have antibodies against N (Tan et al, 2004), N antigen did not induce a detectable serum SARS-CoV-neutralizing antibody response in mice (Buchholz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%